Grip strength measured by high precision dynamometry in healthy subjects from 5 to 80 years - Hogrel, Jean-Yves (BMC musculoskeletal disorders, 2015)
Grip strength is a variable which may be important to measure and follow in various populations. A new dynamometer with high accuracy and sensitivity has recently been developed to assess grip strength. The objectives of this work were to provide norms of maximal isometric grip strength measured with this new dynamometer (the MyoGrip device), to assess the reliability of measurements, to compare the measurements obtained with MyoGrip and Jamar dynamometers and finally to establish predictive equations from a population of healthy subjects (children and adults). Measurements of maximal isometric grip strength using the MyoGrip and the Jamar (which is considered as the gold-standard) were performed on 346 healthy subjects aged from 5 to 80 years. Test-retest reliability for both devices was assessed on 77 subjects. Predictive equations were computed on subjects younger than 60 years of age in order to avoid the effects of aging on strength. This study provides norms for isometric grip strength for health subjects from 5 to 80 years. Reliability of the MyoGrip device was excellent (intraclass correlation coefficient: 0.967). Despite good correlation between devices, the Jamar tended to overestimate maximal grip strength by about 14 %. A single predictive equation for men and women, adults and children incorporating hand circumference only can be used to compute the predicted theoretical maximal grip strength. The MyoGrip device is a reliable tool for measuring isometric grip strength. Owing to its unique metrological features, it can be used in very weak patients or in any situation where high precision and accuracy are required.